The synanthropic flora of kurgans within three steppe zones in southern Ukraine - Sudnik-Wójcikowska, Barbara; Moysiyenko, Ivan I. (Biodiversity: Research and Conservation, 2008)
The aim of the studies conducted in 2004-2008 was to estimate and compare the diversity of synanthropic flora of the kurgans and their microhabitats in three steppe zones in southern Ukraine. Kurgans located among large fields and pastures are very characteristic element of the Ukrainian landscape. Among the 400 visited kurgans, 81 were investigated within an area of about 20 000 km2 in the desert steppe, Pontic grass steppe and herb-grass steppe zones. The total number of species (613), as well as percentage of synanthropic species (55%) was estimated. The number of species on the kurgans in each zone increased along a south-north gradient. However, the percentage of groups of synanthropic species on the kurgans was comparable. Differences between microhabitats (within kurgans) with regard to the proportion of synanthropes were smaller in the case of the desert steppe zone. Contrasts between the microhabitats were more significant in the case of the steppe zones further to the north. The flora of kurgans is determined by the climate conditions of a particular zone and by the form of utilization of the area.